When students write Tape 1 - Ralph Fletcher Joann Potalupi (Stray light media)
Students need to assimilate a daunting numbers of skills as they become competent writers. And this doesn`t happen overnigth. Writing teachers need to create a community where students can live as writers, find their voices, and take the kinds of risks taht allow them to develop competence as writers. In this tape the teachers and principal at Baileys`s elememtary school show how they create that atmosphere.
Area-Documental
Keywords: Genero-Guías educativas